Effect of neem on Phyllocnistis citrella Stainton and its parasitoid Ageniaspis citricola Logvinovskaya in Ecuador - Cañarte-Bermúdez, Ernesto; Navarrete-Cedeño, Bernardo; Montero-Cedeño, Silvia; Arredondo-Bernal, Hugo César; Chávez-López, Onésimo; Bautista-Martínez, Néstor (Enfoque UTE, 2020)
Efficacy of neem on Citrus Leafminer (CLM) and effect on its parasitoid Ageniaspis citricola was evaluated, using field, cage and olfactometer tests. Treatments were: aqueous extract of neem (50 gL-1), formulated oil of neem (10 mL L-1) and control. Field study was done in a Citrus aurantifolia orchard, three applications were carried out, which were evaluated every 48 hours until ten days after the treatment. Cage and olfactometer tests were performed in a greenhouse and repeated twice each time. In the cage, it were used 50 infested Citrus reticulata plants per experimental unit, while for the olfactometer test, as experimental arena, transparent plastic jars with 20 adults of CLM inside were used. Variables evaluated were: CLM infestation, dead, live and predated larvae, pupae, emerged adults and parasitized pupal chambers. The highest mortality of the CLM was caused by the aqueous extract of neem with 77.17%, which began 48 hours after application, suggesting inhibition of feeding. The aqueous extract of neem showed in average 88.80 % of repellency of adults of CLM and neem oil 85.64%. The high mortality of CLM and the repellent effect of neem, seem to influence negatively in parasitism which fluctuated between 9.45 % and 20.16 % in treated trees.